Predictors of Treatment Outcomes among Pediatric Patients Hospitalized with Pneumonia in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Hilina Tsegaw; Mohammed Yimam; Dejen Nureye; Workineh Woldeselassie; Solomon Hambisa (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Pneumonia remains the leading cause of hospitalization and mortality in young children in low- and middle-income countries. This study is aimed to assess predictors of treatment outcomes among pediatric patients hospitalized with pneumonia in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Methods. A facility-based retrospective cross-sectional study was conducted among pediatric patients admitted with pneumonia, considering patient medical charts recorded for a 1-year period from February 2017 to February 2018. The sample size was computed based on a single population proportion formula and giving a total sample size of 207. The systematic random sampling method was employed to select patient cards from the sampling frame. The data extraction format was used to extract any relevant information from patient chart. The processed data were analyzed by using Statistical Package for Social Sciences (SPSS, version 21). Descriptive statistics were used to summarize the patients’ baseline characteristics and related information. The logistic regression model was fitted to determine factors associated with treatment outcomes. To identify predictors of poor treatment outcome, the level of significance was set at P<0.05. Results. From a total of 207 patient charts reviewed, more than half (55.6%) of the study participants were males. Majority of patients, 130 (62.8%), were in the age range of 1 month–11 months. Furthermore, 191 (92.3%) patients had good treatment outcome. Patients who treated with ceftriaxone + azithromycin were less likely to have poor treatment outcome compared with patients who were placed on crystalline penicillin (AOR = 0.86, 95% CI 0.01–0.83). On the contrary, patients who stayed ≥ 8 days were about 14.3 times more likely to have poor treatment outcome compared with patients who stayed ≤ 3 days (AOR = 14.3, 95% CI 1.35–151.1). Conclusion. Even though the study revealed good treatment outcome among the pediatric patients, particular consideration should be given to children in need of other interventions.